INFLUENCE OF LABOR MARKET INSTITUTIONS ON FEMALE YOUTHS’ ACCESS TO FORMAL EMPLOYMENT IN KENYA’S PRIVATE SECTOR - Odundo, Paul Amolloh (Archives of Business Research, 2017)
ABSTRACT Kenya’s demographic trends have resulted in an eminently young population structure. Unfortunately, there is high prevalence unemployment among youths in Kenya. Female youths are the most adversely affected by unemployment. As a result, a good number of them have resorted to seeking employment in the informal sector which in most cases does not provide adequate earnings. It was therefore important to examine the influence of labour market institutions on female youths’ access to employment in the private sector. The study was based on qualitative and quantitative research methodologies. A survey questionnaire and a key informant’s guide were used in collection of quantitative and qualitative data on labor market institutions in Kenya respectively. The study findings revealed that majority of women relied on social networks in gaining employment in the private sector. The findings further indicated that majority of women employees worked under oral contracts that did not guarantee good working conditions. Therefore, existing institutions in the labor market, such as terms and conditions of employment and poor implementation of labor laws hindered female youths’ access to formal employment in the private sector.